Study on Lateral Vibration Characteristic of Gear Rotor Considering Flexibility of Gear Web - Xiannian Kong; Jinyuan Tang (Jixie chuandong)
The aeronautical gear has the characteristics of light weight and low rigidity. It is easy to take lateral vibration under the internal excitation of the gear pair. It is necessary to study the inherent characteristics of the lateral vibration of the aeronautical gear for the design of the aeronautical gear. The flexibility of the gear web， the stiffness of the bearing and the gear meshing stiffness are considered， the finite element model of the gear rotor is established by the finite element software for rotor dynamics named Samcef， and the natural frequency， vibration mode and the critical speed of the high-speed gear rotor system are calculated. Compared with the inherent characteristics of the gear rotor system without consideration of flexibility， it is shown that the frequency values and modes of the lateral vibration of the gear rotor system can be obtained by considering the flexibility of the gear web. Without considering the flexibility of gears， the frequency and mode shapes of lateral vibration of gears can′t be obtained.